Central Serous Chorioretinopathy or a stressful lifestyle predisposes to the disease? - review of the current literature - Dybała, Ewelina; Dybała-Przygrodzka, Izabela; Cuber, Iwona; Mazurek, Magdalena; Białowąs, Edyta; Aghadi, Artur (Journal of Education, Health and Sport, 2023)
Central serous chorioretinopathy (CSCR) is a disease characterized by serous detachment of the neurosensory retina in the macular area, caused by increased choroidal vascular permeability. The disease is more common in young and middle-aged men (20-50 years old), it has been shown to be highly correlated with an increased level of stress in patients. Other risk factors for the central serous chorioretinopathy are: type A personality (ambitious, nervous and emotional people), use of steroids, Cushing’s syndrome, helicobacter pylori infection, gastroesophageal reflux, hypertension, sleep apnea. The disease leads to visual impairment: metamorphopsia, blurred vision, color vision impairment, impaired contrast and vision in the dark. CSCR diagnostics include funduscopic examination of the eye through the Volk lens revealing focus of circular retinal elevation, optical coherence tomography (OCT), which is a quick and non-invasive test that allows the diagnosis and monitoring of the disease. In the past, the diagnosis was based on fluorescein angiography, the dye spilling out fills the detachment space, revealing the leak center. In most cases the shunt stops spontaneously and spontaneous resorption of the subretinal fluid occurs without the need for treatment. The chronic form of CSCR ongoing more than 4 months requires initiation of therapeutic procedures. The first- line treatment is laser therapy. Micropulse laser therapy of the retina stimulates the pigment epithelium to produce anti-angiogenic factors and inhibit the inflammatory process, as a consequence, the resorption of the subretinal fluid occurs with minimal damage to the retina.